Costruire «un immaginario di forza e di possibilità». Intervista con le attiviste del gruppo comunicazione di Lucha y Siesta - Parisi, Stefania; Sciannamblo, Mariacristina (Mediascapes journal, 2021)
This contribution investigates practices, imaginaries and representations delivered by The House of Women Lucha y Siesta, a women's shelter and political collective located in Rome. Based on an in-depth interview with three activists of the House, the contribution explores their perceptions and experiences concerning three thematic areas: the construction of narrative and communication strategies and their dissemination across social networking platforms; the choice of languages and aesthetics and their relationship with the collective imaginary; the role of digital platforms in processes of political participation.